2013
DOI: 10.9790/0853-0921217
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of thumb prints and lip prints among Nigerians

Abstract: Establishment of association between two variables in the forensic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 24 publications
(19 reference statements)
1
7
0
Order By: Relevance
“…11 L H Adamu et al, concluded that type V lip prints was predominant in a study done in Nigerian population. 9 In our study, type I lip prints was found to be predominant in males and type II in females. In the percentage distribution of lip prints the variation noticed with respect to other previous studies may be linked to genetic influences which vary with respect to different races.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…11 L H Adamu et al, concluded that type V lip prints was predominant in a study done in Nigerian population. 9 In our study, type I lip prints was found to be predominant in males and type II in females. In the percentage distribution of lip prints the variation noticed with respect to other previous studies may be linked to genetic influences which vary with respect to different races.…”
Section: Discussionsupporting
confidence: 53%
“…are of paramount importance in solving security findings. 9 Very few studies done in the recent past suggest that a correlative study between the lip print and finger print will be very useful in forensic science for gender identification. 10 Studies of association between finger print and lip prints are scanty in literature.…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that there is inheritance of lip prints in cleft lip and cleft plate in children (Weal et al, 2005). The sexual dimorphic trait reported in lip prints were also associated with genetic influences which vary with respect to different sexes more importantly in sex chromosomes (Adamu et al, 2012).…”
Section: Methodsmentioning
confidence: 98%
“…Finally, a transparent cello tape was used to preserve the print. The print was divided into ten compartments (Adamu et al, 2012 Chi-square test was used to test for association between the variables. Statistical significance was considered at p<0.05.…”
Section: Methodsmentioning
confidence: 99%
“…That is, whether the mouth is opened or closed. An open mouth shows ill-defined grooves while a closed mouth will reveal well defined print patterns and makes interpretation easy [14].…”
Section: Introductionmentioning
confidence: 99%